Integrative Bioinspired Surface with Annular Pattern and Three Dimension Wettable Gradient for Enhancement of Fog Collection - Xinxin Geng; Yan Xing; Jinmu Huan; Yongping Hou; Yongmei Zheng (Advanced Materials Interfaces, 2023)
Abstract A novel integrative bioinspired surface with annular pattern and 3D wettable gradient (APWG) is proposed for fog collection via a simple needle‐face anodic oxidation strategy. The fog collection behaviors are studied on APWG with different pattern types. Such a surface can not only improve the fog droplet capture performance effectively owing to annular wettable gradient pattern, but also realize the fog droplet capture and convergence on different surfaces to accelerate the surface regeneration rate, leading to a further fog collection enhancement. The results of experiment observation and underlying mechanism analysis have certified that such a design can realize a continuous 3D fog collection model to enhance the fog collection efficiency, resulting in a 1345% increase compared to the original surface.